Investigating lenition patterns in south-central Peninsular Spanish /spstsk/ clusters. (21st April 2016) - Henriksen, Nicholas; Harper, Sarah K.
Abstract : In this study we report on an instrumental analysis of /sp st sk / clusters in south-central Peninsular Spanish, documenting a three-way system of /s / realization: speakers tend to produce alveolar fricatives in /st / clusters, velar fricatives in /sk / clusters, and glottal fricatives or deletions in /sp / clusters. An analysis based on the discrete classification of /s / variants shows that a combination of linguistic factors (following consonant and stress) influences /s / realization. An analysis based on the phonetic coding of /s / variants (using measures of fricative duration, relative voicing, and center of gravity) reveals the extent to which velar fricatives display an intermediate status along the phonetic continuum of /s / lenition variations. Taken together, these analyses shed light on the nature of coda /s / in Spanish and on the extent to which the attested allophony constitutes a lenition process.